REKONSTRUKSI TERHADAP DESIGN OF EDUCATION, CHARACTER, AND PRACTICE : (TELAAH ULUL-AL-BAB) - Haris, Abd.; Nurfaika, Nurfaika (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The ideas of scientists expressed in Islamic education are a necessity that must be upheld. The theory and scientific treasures are quite rich in educational concepts that are full of meanings and influence the continuity of an Islamic education in Indonesia. The diversityof educational t eori also arises from two points. Western theory and eastern theory and penetrated into the Islamic education curriculum. Western scientific concepts and ideas are not hypothesized in adding to the treasures of knowledge. However, this is not a guarantee in fulfilling a good spirit and character as a goal of Islamic education. This article aims to examine the reconstruction of educational design, character building by bidding on ulul al-bab as a form of conformity of educational goals with the personality of ulul al-bab. Of course, this paper is based on qualitative-descriptive research. Data collection through review of primary and secondary literature. This means the main reference and supporting reference to this study. This article shows that one of the forms of offers from Muslim intellectuals in realizing the right education, character building and according to the orientation of education in Indonesia, namely the concept and application of ulul al-bab. So that it not only prioritizes education and theory, but is able to explore the meaning of ulul al-bab as an educational solution that cannot be separated from the orientation of Islamic values (value of Islam).